Lean Stability Approaches in Pharmaceutical Product Development, Registration, and Post-marketing CMC Change Management; Industry Survey Insights - Donnie Pulliam; Megan McMahon; Brian P. Regler; Susan Smith; Cheryl Martin; Yelizaveta Babayan; Cherokee Hoaglund-Hyzer; Michael Lesslie; Fenghe Qiu; Eric Adamec; Jin Wang; Pat Forenzo; et al. (Journal of Pharmaceutical Innovation, 2022)
Purpose This paper summarizes results from a recent pharmaceutical industry survey to understand the adoption status of science- and risk-based approaches in pharmaceutical stability (lean stability) in regulatory submissions across the full pharmaceutical product life cycle and to ascertain whether companies are deriving their stability strategies based on scientific risk or applying generic strategies. Methods A comprehensive survey was distributed to pharmaceutical companies affiliated with the International Consortium for Innovation and Quality in Pharmaceutical Development (IQ Consortium) to solicit non-proprietary responses pertaining to regulatory strategies for stability monitoring across the product life cycle, perceived risks, and health authority feedback. Results Among the 19 responding companies, utilization of lean stability approaches varied with respect to (1) phase of product life cycle, (2) specific product quality attributes cited in effective ICH guidances or which demonstrated shelf-life limiting stability trends, and (3) the degree of perceived risk of rejection by health authorities based upon companies’ degree of experience from previous regulatory submissions. Conclusion Continued collaboration between the pharmaceutical industry and health authorities—through case studies and revision/harmonization of regulatory guidances—will be essential for continued implementation of lean stability strategies to accelerate delivery of innovative medicines to the clinic and to the market.

Lean Stability Case Studies—Leveraging Science- and Risk-Based Approaches to Enable Meaningful Phase Specific Pharmaceutical Stability Strategies - Eric Adamec; Yelizaveta Babayan; Bruno Catacchio; Angela Coon; Allison Dill; Mingkun Fu; Lars Gruenig; Cherokee Hoaglund Hyzer; Michael Lesslie; Megan McMahon; Donnie Pulliam; Fenghe Qiu; et al. (Journal of Pharmaceutical Innovation, 2021)
Purpose Lean stability is a science- and risk-based initiative which utilizes the enhanced understanding of drug substance and drug product physical and chemical characteristics to (1) reduce and optimize the design of standard stability protocols; (2) expedite the generation of stability data without impact to safety, efficacy, or quality of the product; and (3) decrease time to market for innovative drugs. Lean stability was introduced in the early 2000s [ICH: Guideline Q1A(R2) (2003), ICH: Guideline Q1D (2002)] followed by reduced stability protocols, focusing on the critical quality attributes and critical time points, being reported in the literature [Skrdla et al. (J Pharm Biomed Anal 50: 794–796, 2009)]. While the concept of lean testing is not entirely new, and it is currently a part of several regulatory guidances, it continues to evolve and gain acceptance of the industry and regulators. Methods In this review, twelve case studies are presented where stability data was collected during clinical, registration, and post-approval phases of the product development. Results Case studies summarize the lean stability testing design, the strategies applied during the regulatory filing and the outcomes of the regulatory filings. Conclusion The authors expect that the case studies presented in this review will increase the visibility of lean stability, facilitate overcoming of the existing challenges, and accelerate the global regulatory acceptance of lean stability practices in the industry.

Src activation of Stat3 is an independent requirement from NF-κB activation for constitutive IL-8 expression in human pancreatic adenocarcinoma cells - Jose G. Trevino; Michael J. Gray; Steffan T. Nawrocki; Justin M. Summy; Donald P. Lesslie; Douglas B. Evans; Tomi K. Sawyer; William C. Shakespeare; Stephanie S. Watowich; Paul J. Chiao; David J. McConkey; Gary E. Gallick (Angiogenesis, 2006)

Multi-Criteria Assessment of Tensions in Resource Use at Continental Scale: A Proof of Concept with Australian Rangelands - Michael J. Hill; Robert Lesslie; Randall Donohue; Paul Houlder; Jane Holloway; Jodie Smith; Kim Ritman (Environmental Management, 2006)